Peran United Nations High Commissioner for Refugee dalam Membantu Kebutuhan Kesehatan Pengungsi Konflik Tigray di Ethiopia (2022-2023) - Widya Pramowardani; Arie Kusuma Paksi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to explain the health conditions of Tigray Conflict refugees and the role of the United Nations High Commissioner for Refugees (UNHCR) in assisting the health needs of Tigray Conflict refugees in Ethiopia in the period 2022-2023. The author uses the theory of international organizations which sees that international organizations have five important roles in resolving problems. This theory is very relevant to the context of the author’s research by looking at UNHCR as an international organization which has one of the five important roles of international organizations, namely as an Aid Provider in resolving conflict in the Tigray region. The type of research used in this article is descriptive, using a library study method which is carried out by collecting data from journals, books, websites and articles as a data collection technique. Based on the results of this research, UNHCR as an international organization working in the field of refugees took part in handling refugees due to the conflict that occurred in Ethiopia, specifically in the Tigray region, namely the conflict between the central government and the Tigrayan People's Liberation Front (TPLF), so the author found that UNHCR had plays a role in providing assistance in the form of basic health services, distribution of vaccines and immunizations, as well as workshops and mental health services.